Automatic packaging equipment for documents - ZHANG LIANG; TANG XIAOHONG; ZHANG FENGSHENG; ZHOU ZHENGSHI (2022)
The invention relates to the technical field of document packaging, in particular to document automatic packaging equipment which comprises a vertically-arranged file bag conveying channel, a channel inlet end is arranged at the bottom of the file bag conveying channel, and the channel inlet end is connected with a file bag feeding device. A bearing sheet capable of moving along the file pocket conveying channel is arranged on the inner side of the file pocket conveying channel; the front side and the rear side of the file pocket conveying channel are provided with a return sheet feeding device, a quintuple sheet feeding device, a gluing device and a heat sealing device respectively. The top of the file pocket conveying channel is connected with a turnover transition piece which can be turned over, and when the turnover transition piece is in a vertical state, an inlet part of the turnover transition piece is in butt joint with the top end of the file pocket conveying channel; when the turnover transition pie